Strumenti di lotta antimafiosa in Italia e in Tunisia - Nabil Zaher (EtnoAntropologia, 2016)
This article aims to speak sicilian instruments to combat anti-mafia in relation to "Le parole sono pietre" written by Carlo Levi and other instruments to combat anti-mafia in relation to the Tunisian Revolution of 2011.